(untitled) (Third Sector Social Economic Review, 2020)
In this study, financial development level of 26 developing Asian and European countries for the period 2013-2017 was analyzed using the OCRA (Operational Competitiveness Rating) method. As financial development indicators, the criteria of the ratio of broad money supply to gross domestic product (GDP), the ratio of bank deposits to GDP, the ratio of domestic credit to the private sector to GDP and the ratio of liquid liabilities to GDP are used. The weight of the criteria used in evaluating the countries examined was calculated by statistical variance procedure. As a result of the study, the level rankings of the developing Asian and European countries were obtained according to the evaluated criteria. Developing Asian countries’ financial development performance (level) was found to be higher than developing European countries. Turkey in terms of the level of financial development is located in the middle row, and is located in the lower ranks according to the new EU member developing European countries.